Further insights into the metamorphosis process in a carapid fish. (29th December 2015) - Parmentier, E.
Abstract: In Carapus homei, settlement on the reef corresponds to a metamorphosis during which the length of the fish is reduced by 60%. This phenomenon is unique since it is the only vertebrate in which the vertebrae are ossified before metamorphosis. Metamorphosis involves the complete degradation and disappearance of the caudal tip vertebrae, and there is a reduction in the size of most of the remaining vertebrae. The aim of this study is to gain more data on the process causing the metamorphosis. The shortening of the body axis can be compared to an 'excision‐splicing' process. During excision, various cell types, including muscle, notochord and osseous vertebrae are progressively lost. Excision causes the spacing of adjacent vertebrae because of the degeneration of their extremities. Splicing allows the shortening of the body by bringing close together the remaining parts of the vertebrae. The mechanism implies a compressive force whose source seems mainly to involve the notochord. The size reduction of the notochordal cells generates the shortening of the notochord along the longitudinal axis and the displacement of the vertebral bodies. At the end of the metamorphosis, the remaining muscles and the highly developed external ligaments of the vertebrae are able to complete the action of the notochord. The study highlights the morphogenetic role of the notochord, which appears to be responsible for the column remodelling and for its final size. The metamorphosis of C. homei represents a highly interesting model for the study of the degeneration, resorption and remodelling of different tissues. Abstract : In Carapus homei, settlement corresponds to a metamorphosis during which the length of the fish is reduced by 60%. The shortening of the body axis can be compared to an 'excision‐splicing' process. Excision causes the spacing of adjacent vertebrae because of the degeneration of their extremities. Splicing allows the shortening of the body. The mechanism implies a compressive force whose source seems mainly to involve the notochord.